2017
DOI: 10.21037/jtd.2017.07.13
|View full text |Cite
|
Sign up to set email alerts
|

Expression of redox sensing factor Nrf2 in lung macrophages and type II pneumocytes as a prognostic factor in pneumothorax recurrence

Abstract: Background: Primary spontaneous pneumothorax (PSP) is a common clinical problem. However, PSP recurrence is still a major concern. Nuclear factor erythroid 2-related factor 2 (Nrf2) plays a protective role against oxidative airway diseases. The aim was to investigate the role of Nrf2 in PSP patients and its correlation with recurrence. Methods: Eighty-nine patients were enrolled and received wedge resection of lung with identifiable blebs.Nrf2 expression in resected lung tissues was determined by immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…NRF2 has previously been shown to regulate chronic lung inflammation through the maturation of dendritic cells and by producing proinflammatory cytokines for priming B cell response to non-typeable H. influenzae (NTHI)-induced airway inflammation in mice [ 40 ]. Furthermore, increased NRF2 expression in alveolar macrophages and type II pneumocytes has been correlated with better incidence-of-recurrence primary spontaneous pneumothorax [ 41 ]. These findings indicate that NRF2 may be exerting a protective effect in normal respiratory epithelium and lung cancer, particularly in this early-stage cohort.…”
Section: Discussionmentioning
confidence: 99%
“…NRF2 has previously been shown to regulate chronic lung inflammation through the maturation of dendritic cells and by producing proinflammatory cytokines for priming B cell response to non-typeable H. influenzae (NTHI)-induced airway inflammation in mice [ 40 ]. Furthermore, increased NRF2 expression in alveolar macrophages and type II pneumocytes has been correlated with better incidence-of-recurrence primary spontaneous pneumothorax [ 41 ]. These findings indicate that NRF2 may be exerting a protective effect in normal respiratory epithelium and lung cancer, particularly in this early-stage cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A total of five studies ( 27 , 30 , 33 - 35 ) examined the association between weight and recurrence, with two showing a significant association. All studies were comparable because they reported the same unit of weight; therefore, they were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…As the primary phagocyte, AMs play a vital role in the local immune defense by initiating the local inflammatory response. Thus, AMs can be used as an indicator to evaluate the pulmonary inflammatory response ( Chiu et al, 2017 ). Our observation reveals that the accumulation of a large number of AMs and inflammatory cell infiltration were clearly observed.…”
Section: Discussionmentioning
confidence: 99%